PELATIHAN PEMBELAJARAN DASAR PEMROGRAMAN MENGGUNAKAN BAHASA PYTHON - Qois Al Qorni; Deka Putra Pamungkas; Suluh Arif Wibowo; Muhammad Fachrurrozi Syawalludin; Teo Yulio Sihotang; Ery Hartati (Politeknik Negeri Sriwijaya, 2023)
In today's digital era, basic programming skills are in high demand in the workplace. Many companies are looking for employees who have basic programming skills to develop more sophisticated applications and technologies. Therefore, it is important for SMK students to have basic programming skills in order to compete in the world of work. This effort can help improve the basic programming skills of SMK children so that they can compete in the increasingly tight world of work and prepare themselves for a better future. This activity involves the stages of pre-test, material delivery, discussion, and post-test. The results show that the students are very happy with this training, which shows that in the first and second questions, the students get new knowledge with a simple explanation carried out by the speaker when conducting training, referring to the initial question before programming training, and after carrying out the training process, the students have 100% gained knowledge. Community service activities entitled